Effectiveness of the Problem-Posing Learning Model on the Learning Outcomes of Seventh-Grade Students at SMP Negeri 1 Palu - Syakinah Novia Putri Pontoh; Rahma Nasir; Mustamin Idris; Tegoeh S Karniman (FKIP - Universitas Riau, 2026)
This study examines the effectiveness of the Problem Posing learning model on mathematics learning outcomes of seventh-grade students at SMP Negeri 1 Palu using a quasi-experimental method with a nonequivalent control group design. A sample of 64 students was selected through cluster random sampling from a population of 352 seventh-grade students across 11 classes at SMP Negeri 1 Palu, with class VII F as the experimental class and class VII J as the control class, each consisting of 32 students. Data were collected via essay-based pretest and posttest, then analyzed using the Kolmogorov-Smirnov normality test, Levene's homogeneity test, independent samples t-test, and N-Gain calculation. The results showed a significance value of 0.048 < 0.05, with the experimental group's N-Gain score (0.66) exceeding the control group (0.57), both in the medium category. Observational findings further confirmed that students in the experimental class were more actively engaged in analyzing mathematical situations, formulating problems, and collaborating with peers, contributing to their higher learning outcomes. Therefore, the Problem Posing learning model is effective in improving students' mathematics learning outcomes, and can serve as a practical alternative for mathematics teachers seeking to enhance student engagement and learning achievement.